Preliminary Identification to Local Coral Bleaching Event in Manjuto Beach, Pesisir Selatan Regency, West Sumatra: Hydro-Oceanographic Perspectives - Ulung Jantama Wisha; Ruzana Dhiauddin; Guntur Adhi Rahmawan; Yusuf Jati Wijaya (Jurnal Ilmiah Perikanan dan Kelautan, 2021)
Highlight ResarchThe cause of local coral bleaching in Manjuto Beash has been addressed.The influence of ebb-tide cycles on salinity mixing and stratification was analyzed.Spatial analysis Digital Shoreline Analysis System (DSASv5) was conducted to determine the coastline changes in Manjuto Beach.Flow model flexible mesh was simulated to determine the flow pattern within Sungai Pinang Bay.AbstractIn October 2019, the local community reported the occurrence of coral bleaching of a colony of Acropora sp. at Manjuto Beach, Pesisir Selatan Regency experienced bleaching. It was published in several local news, becoming a trending topic among local and central government authorities and coastal communities. There were many inaccuracies about the cause of this phenomenon. This study aimed to identify the causes of local coral bleaching in Manjuto Beach based on oceanographic perspectives. The water quality data collected using TOA DKK water quality checker in the surrounding Manjuto Beach were assessed descriptive-statistically. This study also analyzed the spatial changes of the coastline using DSASv5. A time series of tidal data was also used to analyze the tidal range-induced salinity stratification. A flow model with a flexible mesh was also simulated to determine the water mass movement and longshore current patterns in Manjuto Beach. Dissolved oxygen (DO), temperature, and salinity showed anomalies compared to the water quality standard to support marine life. During both flood and ebb tides, it ranged from 5.8-11.2 mg/L, 28-28.3oC, and 25-28 o/oo, respectively. The other parameters measured (pH, conductivity, turbidity, and density) were suitable for marine biota. The findings show that tidal range has a unique influence on salinity stratification. The intrusion of groundwater supply resulted in lowering of salinity, inducing local coral bleaching in Manjuto Beach. Changes in salinity levels were also triggered by tidal current ranging from 0-0.31 m/s resulting in cumulative salinity shock. Currently, Manjuto Beach is experiencing accretion ranging from 2.36-3.17 m/year, altering the water coverage through the flood-ebb cycles. Those states cause cumulative sun rays' exposures and salinity shock induced by flood-ebb cycles. That is why local coral bleaching event is undoubtedly avoided.